SUSTAINABLE HARVESTINGS, PROCESSING AND MARKETING STRATEGIES FOR THE AFRICAN RIVER PRAWN (MACROBRACHIUM VOLLENHOVENII) IN ASEJIRE LAKE, NIGERIA: A VALUE CHAIN ANALYSIS - Oyekanmi, F. B.; Oyekanmi, O.A.; Ekundare, V.O. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The African River Prawn (Macrobrachium vollenhovenii) plays a vital role in supporting rural livelihoods and nutrition around Asejire Lake, Nigeria. Despite its economic potential, the species remains underexploited due to fragmented harvesting, processing, and marketing systems. This study investigates the sustainability of existing value chain activities and proposes strategies for improvement. Using a mixed-methods approach, data were collected through surveys, questionnaires, interviews, focus group discussions, and direct observation involving 220 stakeholders (fishermen (22%), wholesalers (39%), retailers (22%) and consumers (17%). Value chain analysis revealed inefficiencies in gear use, post-harvest losses, and limited market access. Economic assessments highlighted low profitability for primary actors, while sustainability indicators showed vulnerabilities in ecological practices and gender inclusivity. Results showed that prawns (63%), fish (30%) and wild animals (7%) accounted for the total marketed animal products in the study area. Marketing of prawns is by hawking mainly carried out by women (43%) and young secondary school children (57%). The cost benefit ratio showed that fishermen and retailers make substantial profit from prawn sales and there are often travelers who make purchases daily at high prices (N4500.00kg). Prawns were sold fresh (15%), smoked (25%), boiled (48%) or fried 12%). Prawns were valuable as food, bait and as foreign exchange earnings and may be used to substitute fishmeal in fish and livestock feeds. Postharvest loses of products can be reduced if stalls are provided with adequate storage facilities for fresh and dried products. Post harvest losses can be drastically reduced by a well developed organized marketing system or strategies and provision of solar storage facilities to stalls in Asejire Lake at subsidized rates by the government. The study recommends policy interventions, improved extension services, and investments in cold chain infrastructure to enhance value retention and ecological resilience. Findings contribute to the design of inclusive and sustainable value chain models for freshwater prawns in West Africa.